x - 3y = -9
-3y = -9 - x Multiply with -1
3y = 9 + x
4x + 3y= -6
4x + 9 + x = -6
5x + 9 = -6
5x = -6 - 9
5x = -15 Divide with 5
3y=9 + x
3y = 9 +(-3)
3y = 9 - 3
3y = 6 Divide with 3
y = 6/3
x = -3
y = 2
If we note that there is a +3y and a -3y in each of the equations, we simply add the two equations to get:
5x=-15, or x=-3
Substitute x=-3 in either one of the equations to get
Math - We have an important chemsitry test due and I want to make sure that I do...
Intermediate Algebra - Combine like terms: -3x^2+2x-4x^2-9+6x-2x^2+8 Solve for x...
algebra - Solve the indicated variable: 1. Volume of a cone: solve for h: V=Ļir^...
Algebra - Solve for x: h=(k/4)(x-3L) Solve for B: v-6Bxk=7B Solve for S: z+(1/7)...
Algebra - Hi, how would I solve these 2 equations using algebra? It states in ...
Algebra 2 - Solve each system 3x+2y= -2 9x- y= -6 I know how to solve for x but ...
Algebra 2 - How do I solve these inequalities: e^3x>e^x-1 -6log (subscript of...
algebra - solve for the indicated variable: a. temperature formula solve for F: ...
Algebra - FIND THE GCF OF THE PRODUCT (3B+6)(2B-10) SOLVE... X^2=-6X x(x+6)= 0 x...
algebra - im trying to solve a literal equation, then solve the specific ...